STUDY ON FATIGUE CRACK GROWTH RATE BASED ON ELASTIC-PLASTIC MECHANICS (MT) - XU LiDa; ZHANG RuiJin; ZHAO Shuo (Jixie qiangdu)
Definition based on the incremental theory of plasticity of J integral, combining the method of experiment and computer simulation, the method of crack propagation rate based on elastic-plastic mechanics is studied, the research shows that the crack growth rate curve obtained by the incremental plastic J integral is well described the material fracture mechanics performance characteristics, ΔJ integral as the crack growth driving force is verified the rationality of the parameters, in order to further research to explore mechanism of crack extension provides research foundation, a new model is proposed based on the 7N01 aluminum alloy test data, it takes into account the effect of stress ratio on crack propagation, and it is suitable for estimating fatigue life of materials in engineering practice.